Field notes contributed by Dennis L. Carter, July 28, 2005 - Carter, Dennis L.et al (2005)
Summer report of birds found in northeastern Iowa contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2005. Epson - sheet feed